104k views
2 votes
Which expression is equal to (8-3i) - (6 + i)?

14-2i
14-4i
2-2i
2-4i

2 Answers

6 votes

Answer:

2-4i

Explanation:

(8-3i)-(6+i)

distribute right side: 8-3i-6-i

8-6: 2-3i-i

So 2-4i

User Rick Kukiela
by
4.9k points
2 votes

Answer:

2 - 4i

Explanation:

Given expression:


(8 - 3i) - (6 + i)

Apply the distributive law: -(a + b) = -a - b


\implies 8 - 3i - 6 -i

Collect the real part and imaginary part of the complex number:


\implies 8 -6- 3i -i

Simplify:


\implies 2-4i

User Chella
by
4.4k points